Students perceived usefulness towards M-Learning among students of Faculty Educational Studies, UPM - Mahat, Jazihan; Mohd. Ayub, Ahmad Fauzi; Wong, Su Luan (2014)
M-Learning holds a great potential to shift traditional learning into a new paradigm of learning. This paper will focus on examining the students’ perceived usefulness towards M-Learning among students of Faculty Educational Studies, Universiti Putra Malaysia (UPM). This study was based on survey using a set of questionnaire. A pilot test has been carried out among 47 students with the reliability for variable was found over .70. A total of 210 students were selected as a sample of this study based on the random sampling. The finding of this research indicates that Malaysian students have a positive perceived usefulness towards M-Learning.